2020
DOI: 10.7150/ijbs.38264
|View full text |Cite
|
Sign up to set email alerts
|

Innate Lymphoid Cells at the Maternal-Fetal Interface in Human Pregnancy

Abstract: Pregnancy constitutes a major challenge to the maternal immune system, which must tolerate fetal alloantigen encoded by paternal genes. In addition to their role in inducing maternal-fetal immune tolerance, accumulating evidence indicates that decidual immune cells are involved in several processes required for a successful pregnancy, including trophoblast invasion as well as tissue and spiral artery remodeling. Innate lymphoid cells (ILCs), an important branch of the innate immune system, which has expanded r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 171 publications
(210 reference statements)
0
8
0
Order By: Relevance
“…This interaction plays a fundamental role in the induction of intestinal commensal bacteria tolerance [49]. Although altered ILCs numbers have been described in disturbed pregnancies, the role of ILCs in fetal tolerance has not been studied extensively yet [50][51][52][53][54][55]. Our group has previously observed that ILCs reduce their antigen presentation potential during pregnancy, and that uterine ILCs retain a low presentation potential [18].…”
Section: Discussionmentioning
confidence: 99%
“…This interaction plays a fundamental role in the induction of intestinal commensal bacteria tolerance [49]. Although altered ILCs numbers have been described in disturbed pregnancies, the role of ILCs in fetal tolerance has not been studied extensively yet [50][51][52][53][54][55]. Our group has previously observed that ILCs reduce their antigen presentation potential during pregnancy, and that uterine ILCs retain a low presentation potential [18].…”
Section: Discussionmentioning
confidence: 99%
“…We decided to focus this study on key myeloid and NK populations for pregnancy health and their roles in fetal resorption [26,52,84,88,97,98,100,104], however this does not rule out the importance of other immune populations. T cells, NK-T cells, innate lymphoid cells, and trophoblasts all have roles in pregnancy and may play important roles in LPS-mediated uterine inflammation [1][2][3][105][106][107][108][109][110][111][112][113][114][115][116]. Early stages of uterine blood vessel growth, branching, pruning, and remodeling are control.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a second important site of innate immune responses is localized at the decidual layer. The maternal-fetal interface represents the direct contact between the embryo and the mother and it is populated by fetal trophoblast cells, maternal decidual stromal cells (DSCs), and decidual immune cells (DICs) ( 29 ). The decidua is an active site of chemokine synthesis throughout gestation, attracting neutrophils, natural killer cells, dendritic cells, and macrophages ( 17 ).…”
Section: Maternal and Fetal Immune Systemmentioning
confidence: 99%